2020
DOI: 10.32479/ijeep.9653
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Oil and Stock Markets: Evidence From Pakistan Stock Exchange

Abstract: This study documents the impact of price variations in global markets, specifically oil, on stock returns at Pakistan stock exchange (PSX). We select three global markets (oil, gold and currency exchange) and two PSX indices (conventional and Islamic) for a period 2009-2020 to provide evidence. Monthly data for the selected time series is used for analysis. Analysis techniques include descriptive statistics, stationarity testing, Johansen cointegration, correlation and regression analysis. Findings suggest joi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 9 publications
0
13
0
1
Order By: Relevance
“…Government should invest in exploring new reservoirs of crude oil and natural gas. It will reduce the cost of oil import and the outflow of foreign currency for generating electricity (Hanif, 2020). Consequently, increasing the supply of energy to the industries and protects from electricity price shocks (Simon Nicholas & Buckley, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Government should invest in exploring new reservoirs of crude oil and natural gas. It will reduce the cost of oil import and the outflow of foreign currency for generating electricity (Hanif, 2020). Consequently, increasing the supply of energy to the industries and protects from electricity price shocks (Simon Nicholas & Buckley, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…is the previous month price, and Ln is a natural log (Hanif, 2020). Further, adding the control variable like government expenditure, money in circulation, foreign direct investment and wholesale prices can improve the relationship between electricity price and sectoral production.…”
Section: Data Collectionmentioning
confidence: 99%
“…However, if capital inflows aren't adequately distributed, financial uncertainty and contagion may be the result (Das & Manoharan, 2019). An important shortcoming in portfolio diversification that became widely recognised after the GFC [the Global Financial Crisis] as buy-and-and-hold investors started to increasingly use the market as a vehicle for holding investments was that global portfolios had lower diversification and higher volatility (Jiang et al, 2017;Hanif, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies investigating the relationship between oil price movements and macroeconomic variables are more frequently encountered in the literature. In studies investigating the relationship between oil prices and stock markets, it has been found that there is generally a positive relationship between oil markets and stock markets (Sadorsky, 1999;Sadorsky, 2001;El-Sharif et al, 2005;Lescaroux and Mignon, 2008;Bjornland, 2009;Mendoza and Vera, 2010;Wang et al, 2013;Hanif, 2020). In some other studies, the existence of a negative relationship between oil markets and stock markets has been advocated (Filis, 2010;Filis et al, 2011;Cunado and Gracia Perez, 2014).…”
Section: Introductionmentioning
confidence: 98%